Effect of Daily Fiber Intake Among Cirrhotic Patients With and Without Portosystemic Shunts - Simona Parisse; Sara Carnevale; Elio Damato; Flaminia Ferri; Monica Mischitelli; Mario Corona; Pierleone Lucatelli; Alfredo Cantafora; Adriano De Santis; Domenico Alvaro; Maurizio Muscaritoli; Stefano Ginanni Corradini (Current Developments in Nutrition)
Background: A diet rich in fiber, especially soluble fiber, causes cholestatic liver damage and fibrosis in animal models with intestinal dysbiosis, high serum bile acid concentrations, and congenital portosystemic shunts (PSs), but no data on patients with cirrhosis (CIRs) are available. Objectives: To investigate whether dietary fiber consumption was associated with clinical outcomes of CIRs and whether their effect differed according to the presence of PSs. Methods: Daily soluble and insoluble fiber intake was extrapolated from 3-d food diaries in 25 patients with chronic hepatitis (CH) and 80 CIRs outpatient liver transplant candidates abstinent from alcohol and nonviremic for ≥6 mo. In CIRs, the presence of PSs was verified by computed tomography, and the model for end-stage liver disease (MELD) score was calculated at enrollment and after 6 mo. Results: PSs were present in 48 (60%) CIRs. The MELD score after 6 mo, compared with enrollment, had improved in 19 and 10 CIRs with and without PSs, respectively. By adjusting for confounders in logistic regression models we found that improvement in MELD over time was inversely associated with insoluble fiber consumption expressed in milligrams per kilogram (mg/kg) body weight in CIRs without PSs [odds ratio (OR): 0.968; 95% confidence interval (CI): 0.939, 0.997; P = 0.005] but with soluble fiber consumption in CIRs with PSs [OR: 0.946; 95% CI: 0.912, 0.982; P = 0.001]. In CIRs with PSs, soluble fiber consumption was inversely associated with normal serum alkaline phosphatase values at enrollment [OR: 0.964; 95% CI: 0.963, 0.993; P = 0.010]. CHs with normal serum alanine transaminase consumed significantly more soluble fiber (p=0.015) than those with abnormal alanine transaminase. Conclusions: The clinical impact of dietary fiber changes from beneficial to harmful as the stage of chronic liver disease progresses. In particular, in the advanced cirrhosis stage with PSs, soluble fiber intake appears to significantly influence disease progression and should be kept low.